The use of medicinal plants by an indigenous Pataxó community in NE Brazil O uso de plantas medicinais por uma comunidade indígena Pataxó no NE do Brasil - S.T. Lima Cunha; E.D. Rodrigues; C. Alves; T.L. Merrigan; T. Melo; M.L.S. Guedes; A.F. Nascimento; M.B Toralles (Universidade Estadual Paulista, 2012)
We identified and classified 48 medicinal plants used by the Pataxó Indians in south Bahia, Brazil. The location is an ecologically threatened area designated by UNESCO as a World Heritage Site. The aim of this paper is to document phytotherapeutic practices in the indigenous community of Mata Medonha. We conducted interviews with the 25 families present at the area. Of the 48 medicinal species identified, only 14 (29%) had been examined for mechanism of action or isolation of biochemical compounds, according to bibliographic research. The plants were deposited at the Alexandre Leal Costa Herbarium of the Federal University of Bahia. We gathered information about the preparation and uses of the plants. The species are used for a variety of maladies, including flu, congestion, bronchitis and headaches, pain, snake bites, and some were only used for women's disorders. The Pataxó ethnopharmacological knowledge is under pressure from the economic outmigration of the community and threats to the biodiversity from logging, mining, and tourism. The plants studied here include important drug candidates. Additional research on the molecular aspects of the species cited should be performed. Foram identificadas e classificadas 48 plantas medicinais usadas por Índios Pataxós no sul da Bahia. A região é área de risco ecológico designada pela UNESCO como Sítio do Patrimônio Mundial. O objetivo deste estudo foi de documentar as práticas fitoterápicas na comunidade indígena da Mata Medonha. Foram conduzidas entrevistas com as 25 famílias presentes no local. Dentre as 48 espécies identificadas, apenas 14 (29%) foram avaliadas quanto ao mecanismo de ação ou isolamento de compostos químicos, de acordo com levantamento bibliográfico. As plantas foram depositadas no Herbário Alexandre Leal Costa da Universidade Federal da Bahia. Foram registradas informações sobre o preparo e uso das plantas citadas. As espécies são usadas para uma variedade de doenças incluindo gripe, congestão, bronquite, dores em geral, picadas de cobra e algumas apenas para doenças femininas. O conhecimento etnofarmacológico Pataxó está sobre pressão pelas migrações para fora da comuindade e ameaças à biodiversidade por desmatamento, mineração e turismo. As plantas estudadas incluem importantes candidatos a fármacos. Pesquisas adicionais sobre os aspectos moleculares devem ser realizadas.